Church discipline – semper reformanda in Reformation perspective - Duncan, Graham (HTS teologiese studies, 2010)
Church discipline – is semper reformanda in a time and space warp? Church discipline has become an anachronism in the life of the Christian faith community. In part, this results from a misunderstanding of the fundamental meaning of the term. Its early emphasis was on spiritual nurture, discipling people into the faith and into a relationship with one another and God. By the time of the Reformation, it took on a legalistic and rigid form that militated against its earlier approach. This resulted from a misunderstanding of key reformers from the Reforming tradition such as John Calvin and John Knox, who were concerned to build up individuals within the Christian community to become responsible members of society. In this way, discipline is transformative of individuals and society. The work of discipline was closely related both to pastoral care and Christian education and offered a corrective to Medieval discipline, where the concept of discipline was distorted when the use of punitive discipline as a last resort was elevated to become the norm. This situation was replicated in the post-Reformation period. Consequently, it now needs to be rehabilitated in the form of discipling or mentorship in order to restore its usefulness as an educative tool in the process of the pilgrimage towards the kingdom of God.